Cardiovascular Disease Risk Factors Among Blue and White-collar Workers in Indonesia - Nurhayati A Prihartono; Fitriyani Fitriyani; Woro Riyadina (Acta Medica Indonesiana)
Background: cardiovascular diseases (CVD) is the most common cause of death in Indonesia. We aimed to examine risks of CVD in workers aged 40 to 69 year related to their occupational status. Methods: a cross-sectional study in all provinces of Indonesia. Data from a large-scale national health survey called RISKESDAS were used to analyze factors associated with CVD. Analysis was restricted to the working population aged 40 to 69 year. There were 137,378 subjects included in the analysis. Cox’s regression analysis was modified to calculate prevalence ratio for the association of CVD with diabetes mellitus (DM), hypertension, stress, body mass index (BMI), smoking, and particular demographic factors. Results: CVD was associated with occupation; white collar workers were about 1.6 times as likely to be diagnosed with CVD as to blue collar workers.  However, blue collar workers were more likely to report symptoms of CVD than white collar workers. Prevalence of CVD was higher in women than men, increasing by age and education attainment. Hypertension, DM, stress, and increased BMI added the prediction of CVD: prevalence ratio (PR) was 1.72 (95% CI 1.59-1.86), 3.89 (95% CI 3.43-4.44), 3.02 (95% CI 2.77-3.29) and 1.42 (95% CI 1.28-1.57) for BMI ≥27 relative to <25 kg/m2, respectively. The study could not explain the association with smoking. Conclusion: this study added evidence of major risk factors which could be modified to reduce CVD. Some associations were likely to reflect access to health care.